Single-cell analysis using Fourier transform infrared microspectroscopy. Issue 6 (3rd July 2017) - Doherty, James; Cinque, Gianfelice; Gardner, Peter
ABSTRACT: Fourier transform infrared spectroscopy (FTIR) is a well-established, non-destructive method of obtaining chemical information from biological samples such as tissues and cells. This review focuses specifically on the development of infrared spectroscopic microanalysis at the single-cell level. Technological developments, including that of the infrared microscope, synchrotron radiation FTIR, and focal plane array detectors, and their impact on the field are discussed along with the various data processing procedures that are currently used to extract meaningful information. There is then an emphasis on live cell infrared (IR) imaging, including developments in water correction and microfluidic device design. The review concludes with look to future directions, highlighting the potential impact of quantum cascade lasers.